(untitled) (Ameghiniana, 2014)
The graptolite Neurograptus d. N. margaritatus (Lapworth) has been identified for the first time in Argentina. It is described and emphasis is being placed on the inner structure of the thecae, characterized by an orderly system of apertural, ventral and dorsal strips. A brief description of the fossiliferous sequence is a150 given. The age is lower Caradocian, Climacograptus bicornis Zone.